Impact of Media Addiction on Mental Health of Secondary School Students (Gilgit-Pakistan) (Journal of Asian Development Studies, 2023)
This research explores the ramifications of media addiction on the mental health success of secondary students. The primary objective of this study is to find out the impact of media addiction on the mental health of secondary students. Similarly, the hypothesis was formulated, which was that there is no significant impact of social media addiction on mental health. The research employs a quantitative approach, collecting data through a tailored Likert-scale questionnaire that assesses students' perceptions of the identified factors. Subsequently, regression analysis was conducted to ascertain the significance of these factors in predicting academic performance. Upon analyzing the data, the study's conclusions shed light on the specific factors that substantially impact mental health. The results contribute to a better understanding of the complex interplay between students' social media addiction on students' mental health and their educational outcomes. Informed by these findings, recommendations can be made for educators, parents, and school administrators. These recommendations aim to promote effective study strategies, enhance parental involvement, and cultivate self-motivation among students, ultimately fostering an environment conducive to improved academic performance. This research underscores the importance of a holistic approach in addressing social media challenges and provides actionable insights to optimize secondary education practices. The results may also aid in devising targeted interventions and educational strategies to mitigate the adverse effects of media addiction on students' mental health, ultimately promoting a healthier and more productive learning environment.